The Role of Teacher-Student Relatedness and Teachers' Engagement on Students' Engagement in EFL Classrooms - Gan, Shiyuan (Frontiers in Psychology, 2021)
Relationships in language contexts, as well as interactions between teachers and language learners, might play an eminent role in learners’ language ability enhancement. The current review brings to the fore an overview of teacher-student relationships and factors that contribute to this interaction. It has been revealed that EFL teachers’ and learners’ expectations, beliefs, personality, knowledge, and the language teaching context all play a role in creating an adequate relationship among teachers and learners. This overview concludes with how to develop a positive relationship in language classrooms.